DIGITAL FINANCE DAN CLOUD COMPUTING TERHADAP EFISIENSI PROSES AKUNTANSI: LITERATURE REVIEW - Neriana; DP, Rina Tjandra Kirana (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2025)
In the rapidly developing digital era, information technology transformation has become a crucial factor in improving the efficiency of company operations, especially in the field of accounting. This study examines the role of digital finance and the use of cloud computing as the main factors in improving the efficiency of the accounting process. Digital finance enables the automation of financial transactions, reduces manual errors, and accelerates the recording and analysis of financial data. Meanwhile, the implementation of cloud computing provides complexity in data storage, cost efficiency, and increases the accessibility and security of accounting information. The method used in this study is the Systematic Literature Review (SLR) with the PRISMA approach to identify, disseminate, and analyze relevant literature from 2020-2025. The results of the study show that digital finance and cloud computing can improve the efficiency of the accounting process by reducing the burden of manual administration, increasing data accuracy, and supporting faster and more precise data-based decision making. However, challenges such as data security, regulatory requirements, and infrastructure readiness are still obstacles to its implementation. This study provides insight for companies and managers in adopting digital finance and cloud computing as a strategy to improve operational efficiency.